"Slippage" in the talent development environment of elite junior tennis players - Gowling, C. (Coaching and Sport Science Review, 2021)
"Slippage" occurs when there is a mismatch between the intended message communicated (by coach, parent, or talent development environment) and the received message by junior tennis players. The concept of slippage has received attention in educational settings, but research has yet to investigate the possible effects on junior tennis players. The purpose of this study was to examine the experiences of 8 UK, elite junior tennis players and describe what it is like to perform in the elite junior context. An Interpretative Phenomenological Analysis (IPA) of 8 elite junior tennis players (playing LTA Grade 2 and upwards) shows their insights into elite junior tennis. This study found that (a) participants seek meaning behind their tennis experiences and they infer messages from their environment that are not intended, (b) "slippage" is associated with unintentional pressure, and (c) "slippage" is associated with a reduction of junior tennis players` confidence. The findings of this research contribute to an evolving, problematic epistemology of sports coaching and confirms that coaches can lose control of their intended message as players infer their own meanings from interactions within tennis. The findings present governing bodies opportunities to inform coach education literature and consider how the difference between the intended coaching message and the received coaching message can impact the emotional state of junior tennis players.